Perlindungan Hukum Youtuber Atas Publikasi Video yang Telah Dimonetisasi Pendistribusian Royalti oleh Lembaga Manajemen Kolektif - Vernando Samosir, Anju Doli; Christine S.T. Kansil (Universitas Ekasakti, 2023)
The existence of regulations regarding Collective Management Institutions (LMK) in Law 28/2014 and the existence of monetization on YouTube should prevent YouTubers from copyright violations, because Article 87 of Law 28/2014 regulates that the use of works and/or is not considered a violation of Law 28/2014. Related Rights products commercially by users as long as the user has carried out and fulfilled the obligations in accordance with the agreement with LMK. However, there is one very interesting case to be studied in Decision 41PK/Pdt.Sus-HKI/2021 where the Defendant is the creator and owner of video content through the account/channel of YouTuber Gen Halilintar which has been monetized and has paid royalties to LMK, namely Wahana Musik Indonesia (WAMI) was sued by PT Nagaswara Publisherindo which is the copyright holder of a song creation (music and lyrics) entitled